Rapid development of neurological infection in a patient with human immunodeficiency virus following schistosomiasis: A case report - Yan Liu; Guoqiang Zhou; Wei Jiang; Xianglong Kong (iLabmed)
Abstract HIV‐1 and schistosomal infections present significant global health challenges, and neurological manifestations of these pathogens are easily misdiagnosed due to their rarity. Here, we report the case of a 36‐year‐old patient with acquired immunodeficiency syndrome who was initially diagnosed with human immunodeficiency virus‐1 (HIV‐1) infection 4 years earlier, although untreated for approximately 3 years until he began antiretroviral therapy (ART) following a tuberculosis diagnosis and hospitalization. Despite achieving virological suppression of HIV‐1 1 year after ART, he was readmitted with high fever and headache. Initial therapy for suspected tuberculosis based on clinical performance and brain imaging features failed, and further investigation confirmed an intracranial infection caused by schistosomiasis. Following anti‐schistosomal treatment and optimized ART, the patient recovered fully and was discharged. This case of a patient in Asia infected with human immunodeficiency virus (HIV) who rapidly developed a neurological infection subsequent to acquiring schistosomiasis highlights the need for awareness of such coinfections in patients with HIV.